2011
DOI: 10.1093/infdis/jir725
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent-Activated Transfected Killer Cells to Monitor Leukocyte Trafficking During Systemic Bacterial and Fungal Infection

Abstract: ATAK cells accumulated in target organs with distinct profiles, depending on the microbial etiology of infection. Finally, generation of an anti-ATAK immune response may provide an important safety mechanism that helps clear the cells from the host as the marrow recovers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Most of our current knowledge about neutrophil function in the setting of A. baumannii infection originates from mice treated with cyclophosphamide, ( Qiu et al, 2009 ; Lin et al, 2012 ; Manepalli et al, 2013 ; Thompson et al, 2014 ; Bruhn et al, 2015 ) a cytotoxic alkylating agent widely used for the treatment of neoplastic and severe autoimmune diseases. Cyclophosphamide suppresses myelopoiesis resulting in neutrophil depletion in murine models ( Zuluaga et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of our current knowledge about neutrophil function in the setting of A. baumannii infection originates from mice treated with cyclophosphamide, ( Qiu et al, 2009 ; Lin et al, 2012 ; Manepalli et al, 2013 ; Thompson et al, 2014 ; Bruhn et al, 2015 ) a cytotoxic alkylating agent widely used for the treatment of neoplastic and severe autoimmune diseases. Cyclophosphamide suppresses myelopoiesis resulting in neutrophil depletion in murine models ( Zuluaga et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…cerevisiae and in other pathogenic organisms such as C . albicans [ 16 ], [ 24 ], [ 32 ]. The results revealed that only 15% of mice infected with strain D14 survive until day 22, whereas D14Δgua1 was unable to cause death in the mice.…”
Section: Resultsmentioning
confidence: 99%
“…Antifungal therapy failured to manage the infection due to the presence of hyphae, the main feature of the fungus that allows it to penetrate blood vessels, and this prevents the penetration of antifungal agents into the fungus (Mehrad et al, ). Studies conducted have shown that neutrophils display potent anti‐ Aspergillus activity, exhibiting efficient migration to sites of fungal infection (Farowski et al, ; Lin et al, ; Lin, Ibrahim, Baquir, Palosaari, & Spellberg, ; Todeschini et al, ). It has been also found that posaconazole, a broad‐spectrum antifungal, accumulates in large concentrations in leukocytes, especially in neutrophils (Campoli et al, ; Conte Jr. et al, ; Hof, ).…”
Section: Neutrophil‐targeted Drug Delivery In Respiratory Diseasesmentioning
confidence: 99%